Causes of farmer-herder conflicts in the commune of Sio, Mopti Region, Mali - Ba, El Hadji Boubacar; Ba, Baba (CGIAR System Organization, 2025)
This study, conducted in the commune of Sio in the Mopti Region of Central Mali, aimed to analyze the root causes and impacts of conflicts between farmers and herders. This agropastoral territory is significantly affected by profound socio‐spatial transformations, increasing pressure on natural resources exacerbated by climate variability and a persistent security crisis. The interaction of these factors has intensified rivalries among rural communities, undermined social cohesion, weakened livelihoods, and posed serious threats to food security.